تطور الفن المسرحي العربي واتجاهاته في نيجيريا : دراسة تحليلية نقدية - صارم، عبد الكريم عيسى (International Islamic University Malaysia, 2014)
This work centers on Arabic Drama in Nigeria, one among of the varieties of Arabic prose works written by indigenous Arabic writers. It's also to narrate and analyze both the trend and context of such literary genres as cultivated by those writers. The objective of this work is to indeed showcase another phase of Arabic literary work outside the belt-fold of the native speakers, while the significance is to draw the audience's attention to one of the most closest literary genres that clearly mirrors man's life, Socially, culturally, politically and Religious wise. This dissertation covers only the playwright work done by Nigerian Arabists, between the period of 1990- 2012, and narratively analyzed the trend and context of fifteen best selected among those literary works.